S127 Relation between change in type 2 biomarker levels and efficacy outcomes in patients with asthma treated with dupilumab. (11th November 2022) - Pavord, ID; Deniz, Y; Casale, T; Corren, J; FitzGerald, JM; Altincatal, A; Gall, R; Pandit-Abid, N; Radwan, A; Jacob-Nara, JA; Rowe, PJ; Busse, WW
Abstract : Background: Type 2 inflammation is associated with elevated levels in biomarkers including, among others, fractional exhaled nitric oxide (FeNO) and blood eosinophils. Dupilumab, a fully human monoclonal antibody, blocks the shared receptor component for IL-4 and IL-13, key and central drivers of type 2 inflammation. In the QUEST study (NCT02414854 ), add-on dupilumab 200 mg and 300 mg every 2 weeks, versus matched placebo, significantly reduced severe asthma exacerbations and improved pre-bronchodilator forced expiratory volume in 1 second (FEV1 ) in patients with uncontrolled, moderate-to-severe asthma. Effects were greater in patients with elevated type 2 biomarkers at baseline. This post hoc analysis evaluated the relationship between changes from baseline in blood eosinophil and FeNO levels, and efficacy endpoints in the intention-to-treat (ITT) population of the QUEST study. Methods: Annualized rate of severe exacerbations (AER) during the 52-week treatment period and change from baseline in pre-bronchodilator FEV1 at Week 52 were derived as functions of fold change in blood eosinophils at Week 12 and FeNO levels at Week 52, using penalized regression spline models. Results: The dupilumab group showed lower AERs compared with the placebo group across all fold change values of blood eosinophils and FeNO change examined, and a higher pre-bronchodilator FEV1 than the placebo group across all values of eosinophils fold change ( figure 1 ). Greater reductions in FeNO levels correlated with greater improvements in pre-bronchodilator FEV1 at Week 52 ( figure 1 ). Conclusions: In patients with uncontrolled, moderate-to-severe asthma, dupilumab lowered the AER compared with placebo regardless of the magnitude of eosinophil and FeNO reduction, and improved FEV1 regardless of the magnitude of eosinophil change. Greater reductions in FeNO levels at Week 52 were associated with greater improvements in pre-bronchodilator FEV1 with dupilumab compared to placebo by end of treatment, which points to the utility of FeNO to predict responsiveness to dupilumab. Please refer to page A212 for declarations of interest related to this abstract.